0761 Independent Components Analysis And Graph Theoretical Analysis In Patients With Narcolepsy. (27th May 2020) - Xiao, F; Zhao, L; Han, F
Abstract: Introduction: To evaluate resting state functional connectivity and topological properties of brain network in narcolepsy compared with healthy controls. Methods: Resting state fMRI was performed in 26 adult narcolepsy patients and 30 matched healthy controls. MRI data was first analyzed by group independent component analysis, then a graph theoretical method was applied to evaluate topological properties within whole brain. Small-world network parameters and nodal topological properties were measured. Altered topological properties in brain areas between groups were selected as ROI-seeds, then functional connectivity among these ROI-seeds were compared between groups. Partial correlation analysis was performed to evaluate the relationship between sleepiness severity and functional connectivity or topological properties in the narcolepsy. Results: 21 independent components out of 48 components were obtained. Compared with healthy controls, narcolepsy exhibited a significant decreased functional connectivity within the executive and salience network, while increased functional connectivity in bilateral frontal lobe within executive network can be detected in narcolepsy. There were no differences in small-world network properties between narcolepsy and healthy controls. The altered brain areas in nodal topological properties were mainly located in inferior frontal cortex, basal ganglia, anterior cingulate, sensory cortex, supplementary motor cortex and visual cortex between groups. In the partial correlation analysis, nodal topological properties in putamen, anterior cingulate and sensory cortex as well as functional connectivity between these brain regions were correlated with the severity of sleepiness (sleep latency, REM sleep latency and ESS) among narcolepsy. Conclusion: Altered connectivity within executive network and salience network were found in narcolepsy. Functional connection changes between left frontal cortex and left caudate nucleus may be one of the parameters describing the severity of narcolepsy. Nodal topological properties alterations in left putamen and left posterior cingulate, changes in functional connectivity between left supplementary motor area and right occipital as well as changes in functional connectivity between left anterior cingulate gyrus and bilateral postcentral gyrus can be considered to be a specific indicator for evaluating the severity of narcolepsy. Support: National Natural Science Foundation of China (81700088)National Program on Key Basic Research Project of China (973 Program, 2015CB856405)